Friction and Wear Resistance for Polyetheretherketone Filled with Different Filler Materials: A Comparative Study - Mustafa, Dalia M.T.; Rostam, Sarkawt (Kurdistan Journal of Applied Research, 2017)
Friction and wear behavior of Polyetheretherketone (PEEK) filled with different filler composites were compared. The comparisons were made for different scholar research works which were published between 1987 – 2017.The comparison took place between different filler composites such as carbon fiber (CF) reinforced Polyetheretherketone, nanometer Al2O3, nanometer SiC, polytetrafluoroethylene (PTFE) filled PEEK, nanometer ZrO2, nanometer SiO2, nanometer Si3N4, CuS, short fiber reinforced PEEK composites, PEEK-CF30, GO-Si and Graphite composites.The friction and wear were studied according to different factors of the filler composites such as plasma treated PEEK, volume percentage, weight percentage, sliding distance, surface of roughness, and size of particles.By this work we can understand the effect of some nanometer particles which act as fillers in polyetheretherketone, and by this comparison study we conclude that friction and wear properties can be decreased or increased or stay unchanged by increasing and decreasing the amount of fillers but it can be improved by adding different fillers with certain properties to obtain optimal results.